Back to the Future. The Aftermath of Poland’s 2023 Parliamentary Election (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
On 15th October 2023 Polish voters decided to put an end to the 8-year period of the Law and Justice Party in power, widely seen as “authoritarian populism”. The paper analyses the electoral programmes of the major contenders (Law and Justice, Civic Coalition, Third Way, New Left and Confederation) as well as a variety of election-related statistics (e.g. by voters’ age, education, occupation and residence) revealing a more complex image of the Polish society and its political preferences in 2023. The author argues that due to remarkable ideological and socio-cultural polarization contemporary Poland remains “a house divided” or even “two nations [with] no sympathy [for each other]”. Even if Poland has now chosen a path back to the future, the new pro-EU liberal government will face a number of identifiable challenges.
Keywords: Poland; Polish Election of 2023; Law and Justice (PiS); Populism; “Democratic Opposition”